Stress Hyperglycemia: A Problem that Cannot be Ignored - Peng, Daxu; Zhang, Yifan; Cao, Xiuyang; Pu, Jianyi (Journal of Endocrinology Research, 2022)
Stress hyperglycemia is a strong neuroendocrine reaction in thehypothalamic pituitary adrenal cortex under severe infection, trauma, burns,hemorrhage, surgery and other harmful stimulated, resulting in increasedsecretion of counter-regulatory hormones. These hormones promotedthe production of sugar and cause glucose metabolism disorders withcytokines and insulin resistance. In this condition, the production of sugarexceeds the utilization of sugar by the tissues, which eventually leads to anincrease in blood glucose levels in plasma. In the intensive care unit, stresshyperglycemia is very common and can occur in patients with or withoutdiabetes. The incidence is as high as 96%, and it is an independent factorin the death of critically ill patients. Hyperglycemia not only prolongsthe hospitalization time, mechanical ventilation time and increased theincidence of serious infections in critically ill patients, but can also leadto the occurrence of type 2 diabetes. Therefore, it is very important tolearn the pathological mechanism of stress hyperglycemia, the harm ofhyperglycemia and blood sugar management.